Low-temperature heating in existing Swedish multi-family houses—An assessment of the significance of radiator design and geometry. (3rd April 2017) - Wang, Qian; Ploskić, Adnan; Holmberg, Sture
Abstract : The current study evaluates the impacts of radiator designs and geometries. The aim was to map the thermal efficiency and performance differences of studied radiator types. A typical Swedish low-rise, multi-family house was selected to present the analysis. A Swedish climate was employed to evaluate the applicability. The on-site measurements, analytical model, and real-life performance data from radiator manufacturing were applied for the modeling work. Radiator Type 21 (1.2 × 0.4 m) showed the highest exergy efficiency; Type 11 (1.2 × 0.45 m), the lowest. There is no evidence that Type 22 (adding more convector plate) has a higher thermal efficiency than Type 21, from an engineering perspective, within the climate range of −20°C to 15°C. Baseboard radiators showed a 34% higher exergy performance than the most efficient conventional radiator, with the same surface area, at mean outdoor temperatures during an average heating season in Sweden (−1.3°C). The results also suggest that Type 21 would have higher efficiency than Type 11 during 50% time of the heating season, in severe climate conditions. In the climate of Stockholm, this efficiency advantage was 20%. For the mild climate, Type 11 and Type 21 performed almost the same over the entire heating season.